2015
DOI: 10.1002/2015ja021443
|View full text |Cite
|
Sign up to set email alerts
|

Resolute Bay Incoherent Scatter Radar observations of plasma structures in the vicinity of polar holes

Abstract: The Resolute Bay Incoherent Scatter Radar North (RISR‐N) data collected between January 2012 and June 2013 are employed to identify and analyze 14 events with significant plasma density depressions (Ne<4 × 1010 m−3) in the winter polar cap ionosphere. The RISR‐N observations near a magnetic latitude (MLAT) of 85°N refer to the region poleward of the previously identified polar hole‐auroral cavity region 70°–80° MLAT where extremely low densities (down to 2 × 108 m−3 near 300 km in altitude) are found at tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 41 publications
4
9
0
Order By: Relevance
“…This is consistent with the Doppler velocity measured by MCM within the patch (dark blue colors). Similar consistency between the patch drift and plasma convection velocities was observed by Bristow et al [] using MCM observations and, more recently, by Makarevich et al [] using direct observations of 2‐D convection velocity and density enhancements by RISR‐N in the northern polar cap. This implies that polar patches tend to move with the background convection, at least deep within the polar cap.…”
Section: Discussionsupporting
confidence: 87%
“…This is consistent with the Doppler velocity measured by MCM within the patch (dark blue colors). Similar consistency between the patch drift and plasma convection velocities was observed by Bristow et al [] using MCM observations and, more recently, by Makarevich et al [] using direct observations of 2‐D convection velocity and density enhancements by RISR‐N in the northern polar cap. This implies that polar patches tend to move with the background convection, at least deep within the polar cap.…”
Section: Discussionsupporting
confidence: 87%
“…Particle precipitation is another process that can produce plasma enhancements (e.g., Oksavik et al, ) and change the background electron density within the structures brought to the polar cap by convection (Goodwin et al, ; Makarevich et al, ). It is common to divide the precipitation events in the polar ionosphere into three types: polar rain, polar showers, and polar squalls.…”
Section: Discussionmentioning
confidence: 99%
“…The density criterion in this study is stricter in comparison to other studies. For example, Makarevich et al (2015) investigated events where 1% of RISR-N measurements at 300 km had N e < 4 × 10 10 m −3 and at least 10% of measurements with N e < 10 11 m −3 . Additionally, the study of Crowley et al (1993) indicated the polar hole in the Qanaq digisonde N m F 2 observations as a drop from 4 × 10 11 m −3 to 10 11 m −3 , which is not as deep as what was considered here.…”
Section: Observationsmentioning
confidence: 99%